Efficiency in a search and matching economy with a competitive informal sector - Olivier Charlot; Franck Malherbet; Mustafa Ulus (Institute for the Study of Labor (IZA), 2012)
We consider a dual labor market with a frictional formal sector and a competitive informal sector. We show that the size of the informal sector is generally too large compared to the optimal allocation of the workers. It follows that our results give a rationale to informality-reducing policies.
Keywords: E24; E26; J60; L16; O1; 330; search and matching models; informality; efficiency; Dualer Arbeitsmarkt; Matching; Informeller Sektor; Allokationseffizienz; Theorie